The Two Cultures in Psychiatry - Cleghorn, R. A. (1965)
The division between the two cultures of the literary and scientific worlds is considered, as is the division between the two cultures of humanism and somaticism. The development of psychiatric thought important to this latter dichotomy is described through the Age of Enlightenment, the Romantic Movement and the New Enlightenment. The two cultures of our present literary and scientific milieux are equated with the romanticism and somaticism of the past. The development of two cultures in psychiatry is traced, beginning with Freud's attempt to combine science and romanticism, to the present day where one finds some degree of convergence between the somatic and psychoanalytic approaches. Criteria are presented for a greater union of the two cultures in psychiatry.